Innate Immunity Holding the Flanks until Reinforced by Adaptive Immunity against Mycobacterium tuberculosis Infection - Khan, Nargis; Vidyarthi, Aurobind; Javed, Shifa; Agrewala, Javed N. (Frontiers in Microbiology, 2016)
T cells play a cardinal role in imparting adaptive immunity against Mycobacterium tuberculosis (Mtb). However, ample time is required before T-cells are able to evoke efficient effector responses in the lung, where the mycobacterium inflicts disease. This delay in T cells priming, which is termed as lag phase, provides sufficient time for Mtb to replicate and establish itself within the host. In contrast, innate immunity efficiently curb the growth of Mtb during initial phase of infection through several mechanisms. Pathogen recognition by innate cells rapidly triggers a cascade of events, such as apoptosis, autophagy, inflammasome formation and nitric oxide production to kill intracellular pathogens. Furthermore, bactericidal mechanisms such as autophagy and apoptosis, augment the antigen processing and presentation, thereby contributing substantially to the induction of adaptive immunity. This manuscript highlights the role of innate immune mechanisms in restricting the survival of Mtb during lag phase. Finally, this article provides new insight for designing immuno-therapies by targeting innate immune mechanisms to achieve optimum immune response to cure TB.